2020
DOI: 10.1016/j.semarthrit.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in Juvenile Myositis patients

Abstract: Objective-Juvenile idiopathic inflammatory myopathies (JIIM) are rare, chronic autoimmune muscle diseases of childhood, with the potential for significant morbidity. Data on long-term outcomes is limited. In this study we investigate correlations between clinical and demographic features with long-term outcomes in a referral population of adult patients with JIIM.Methods-Forty-nine adults with JIIM were assessed at two referral centers between 1994 and 2016. Features of active disease and damage at a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
13
2
Order By: Relevance
“…It is possible that perceived muscle weakness for example may be impacted by several factors including cardiorespiratory fitness, endurance, physical disability, or psychological wellbeing. However, the fact that over one-third of patients reported muscle weakness at the time of the questionnaire is comparable to other studies that demonstrate impaired muscle strength and cardiorespiratory fitness compared to healthy controls many years after the diagnosis of JDM [27,37,38].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…It is possible that perceived muscle weakness for example may be impacted by several factors including cardiorespiratory fitness, endurance, physical disability, or psychological wellbeing. However, the fact that over one-third of patients reported muscle weakness at the time of the questionnaire is comparable to other studies that demonstrate impaired muscle strength and cardiorespiratory fitness compared to healthy controls many years after the diagnosis of JDM [27,37,38].…”
Section: Discussionsupporting
confidence: 81%
“…In comparison with 3 other long term outcome studies reporting the HAQ (median 0, IQR 0–0.3 [ 26 ], median 0.4, IQR 0–1.0 [ 27 ], mean 0.2, SD 0.5, range 0–1.9 [ 2 ]), our cohort had better HAQ scores despite reports of persistently active disease.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Strengths of our study include that 95% of all identified and tracked JDM patients participated in the study; our results are thus less biased toward serious cases compared to other outcome studies [ 42 ]. Since our age- and sex-matched controls were randomly drawn from the Norwegian registry, we believe they reflect the general population.…”
Section: Discussionmentioning
confidence: 99%